BULBAR DYSARTHRIA - Iminjonova Mokhichehra Alimardon qizi (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2025)
ABSTRACT: Bulbar dysarthria is a severe speech disorder resulting from damage to the bulbar centers located at the brainstem level, specifically the nuclear complexes of the IX, X, XII cranial nerves and their associated neural pathways. In this condition, the processes of articulation, phonation, respiratory-speech coordination, and swallowing are severely impaired. This study examines the etiology, pathogenesis, clinical signs, diagnostic approaches, and speech therapy rehabilitation strategies for bulbar dysarthria. It provides an in-depth analysis of the consequences of peripheral damage to the speech motor system and highlights modern assessment techniques (acoustic analysis, articulatory monitoring, clinical screening) and corrective programs used in patient treatment. The material systematically compiles the theoretical foundations of bulbar dysarthria and describes effective methods employed in practical speech therapy.